Failure of Recombinant Activated Factor VII in Treatment of Diffuse Alveolar Hemorrhage due to Cryoglobulinemic Vasculitis. (9th July 2014) - Khoulani, Dania; Rao, Bharat; Khanshour, Ammar; Kuriakose, Philip; Yessayan, Lenar
Abstract : Diffuse alveolar hemorrhage (DAH) is a serious complication of the small vessel vasculitis syndromes and carries a high mortality. Recombinant activated factor VII (rFVIIa) is used to treat bleeding in patients with hemophilia and antibodies to factor VIII or IX. It is increasingly being used in life-threatening hemorrhage in a variety of other settings in which conventional therapy is unsuccessful. Randomized controlled trials of rFVIIa in DAH are lacking. However, several case reports have described a complete or sustained control of DAH using rFVIIa after patients failed to respond to medical treatment. There are no case reports in the literature describing the use or the failure of rFVIIa in DAH associated with cryoglobulinemic vasculitis. We here report the failure of rFVIIa to control DAH in a patient with CD5+ B-cell non-Hodgkin's lymphoma and cryoglobulinemic vasculitis.